Do Clinicians Use Online Evidence to Support Patient Care? A Study of 55,000 Clinicians - Westbrook, Johanna I. (American Medical Informatics Association, 2004)
Objectives: To determine clinicians' (doctors', nurses', and allied health professionals') “actual” and “reported” use of a point-of-care online information retrieval system; and to make an assessment of the extent to which use is related to direct patient care by testing two hypotheses: hypothesis 1: clinicians use online evidence primarily to support clinical decisions relating to direct patient care; and hypothesis 2: clinicians use online evidence predominantly for research and continuing education. Design: Web-log analysis of the Clinical Information Access Program (CIAP), an online, 24-hour, point-of-care information retrieval system available to 55,000 clinicians in public hospitals in New South Wales, Australia. A statewide mail survey of 5,511 clinicians. Measurements: Rates of online evidence searching per 100 clinicians for the state and for the 81 individual hospitals studied; reported use of CIAP by clinicians through a self-administered questionnaire; and correlations between evidence searches and patient admissions. Results: Monthly rates of 48.5 “search sessions” per 100 clinicians and 231.6 text hits to single-source databases per 100 clinicians (n = 619,545); 63% of clinicians reported that they were aware of CIAP and 75% of those had used it. Eighty-eight percent of users reported CIAP had the potential to improve patient care and 41% reported direct experience of this. Clinicians' use of CIAP on each day of the week was highly positively correlated with patient admissions (r = 0.99, p < 0.001). This was also true for all ten randomly selected hospitals. Conclusion: Clinicians' online evidence use increases with patient admissions, supporting the hypothesis that clinicians' use of evidence is related to direct patient care. Patterns of evidence use and clinicians' self-reports also support this hypothesis.